2021
DOI: 10.3390/biom11121804
|View full text |Cite
|
Sign up to set email alerts
|

Tempol Alters Urinary Extracellular Vesicle Lipid Content and Release While Reducing Blood Pressure during the Development of Salt-Sensitive Hypertension

Abstract: Salt-sensitive hypertension resulting from an increase in blood pressure after high dietary salt intake is associated with an increase in the production of reactive oxygen species (ROS). ROS are known to increase the activity of the epithelial sodium channel (ENaC), and therefore, they have an indirect effect on sodium retention and increasing blood pressure. Extracellular vesicles (EVs) carry various molecules including proteins, microRNAs, and lipids and play a role in intercellular communication and intrace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 36 publications
0
16
0
Order By: Relevance
“…After incubation on ice for 10 min, 2 mL methanol, and 0.9 mL methylene chloride were added and the solution was vortexed for 30 s. EquiSPLASH Lipidomix (Avanti Polar Lipids, Inc., Alabaster, AL, USA), a mixture of 13 deuterated lipids was used as an internal standard. The composition of the internal standard mixture was described in our previous publication [ 14 ]. The internal standard was diluted 5 times using cold methanol to adjust each deuterated lipid’s concentration to 20 µg·mL −1 , and then 50 µL was spiked into each sample.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…After incubation on ice for 10 min, 2 mL methanol, and 0.9 mL methylene chloride were added and the solution was vortexed for 30 s. EquiSPLASH Lipidomix (Avanti Polar Lipids, Inc., Alabaster, AL, USA), a mixture of 13 deuterated lipids was used as an internal standard. The composition of the internal standard mixture was described in our previous publication [ 14 ]. The internal standard was diluted 5 times using cold methanol to adjust each deuterated lipid’s concentration to 20 µg·mL −1 , and then 50 µL was spiked into each sample.…”
Section: Methodsmentioning
confidence: 99%
“…Collectively, uEVs have been demonstrated to be enriched in important renal transport proteins including aquaporins [ 10 , 11 ] and epithelial sodium channels [ 12 , 13 ]. Recent studies have demonstrated that uEVs are a rich source of biomarkers and can be useful in the pathogenesis of hypertension [ 14 ]. Although the excretion of EVs into the urine varies on a myriad of stressors [ 15 , 16 ], drug treatments [ 17 ], temperature changes [ 18 ], and social habits [ 19 ], little is known about the excretion of EVs into the urine during the inactive and active phases of any animal or rodent model.…”
Section: Introductionmentioning
confidence: 99%
“… 70 For serum-derived EVs are notable in bipolar disorder, 73 COVID-19, 74 Alzheimer’s disease, 50 , 75 The whole blood has been displayed on breast cancer. 47 Urine tissue are always applied to research on kidney and prostate, such as salt-sensitive hypertension, 78 and prostate cancer (PCa). 79 Auditory cell-derived EVs has been utilized in drug- and noise-related hearing loss.…”
Section: How Potential Of Metabolomics Of Extracellular Vesicles In C...mentioning
confidence: 99%
“…EVs carry cargo in the form of genetic material (small RNA species, including miRNAs), proteins, and lipids, and can transfer their heterogeneous cargo to target cells to induce biological responses 40 . For this reason, EVs have been considered as therapeutic agents for several conditions including those where multiple molecules and/or pathways are missing or dysregulated, such as asthma, chronic lung disease, diabetes, systemic hypertension, and cancer 41–49 …”
Section: New Insights Into Molecular Mechanisms Of Pulmonary Hypoplas...mentioning
confidence: 99%
“…40 For this reason, EVs have been considered as therapeutic agents for several conditions including those where multiple molecules and/or pathways are missing or dysregulated, such as asthma, chronic lung disease, diabetes, systemic hypertension, and cancer. [41][42][43][44][45][46][47][48][49]…”
Section: New Insights Into Molecular Mechanisms Of Pulmonary Hypoplas...mentioning
confidence: 99%